4x-3-3(2x)=12+3x

Simple and best practice solution for 4x-3-3(2x)=12+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3-3(2x)=12+3x equation:



4x-3-3(2x)=12+3x
We move all terms to the left:
4x-3-3(2x)-(12+3x)=0
We add all the numbers together, and all the variables
4x-32x-(3x+12)-3=0
We add all the numbers together, and all the variables
-28x-(3x+12)-3=0
We get rid of parentheses
-28x-3x-12-3=0
We add all the numbers together, and all the variables
-31x-15=0
We move all terms containing x to the left, all other terms to the right
-31x=15
x=15/-31
x=-15/31

See similar equations:

| (2x+15)+6=180 | | 50=-8z-2z | | 50=-8z–2z | | 3(u+3)=15 | | u/5+8=38 | | 9x-14=25 | | f(-4)=3(-4)-2 | | 7t+4=102−7t | | 5(z-2)+3z=1 | | 2x+2=x+ | | 10x+5=5x+60 | | y=-25(0)+170 | | 2f+7f+9=0 | | 3x(2)+2x=360 | | 4(1+4x)= | | 4x+14=6x-10 | | x+9=-2x+24 | | -7w+5w+2+4=0 | | 70x+4x=1500 | | 2x+11=5x+23 | | 2(4x5)-3=5x(2+1) | | 3x-3=-3x+15 | | 3=5v-2 | | (x-(x-1)/5-2)/5+(x-(x-1)/5-(x-(x-1)/5-2)/5-6-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-4-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-5-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-4-(x-(x-1)/5-(x-(x-1)/5-2) | | (x-(x-1)/5-2)/5+(x-(x-1)/5-(x-(x-1)/5-2)/5-6-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-4-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-5-(x-(x-1)/5-(x-(x-1)/5-2)/5-3)/5-(x-(x-1)/5-(x-(x-1)/5-2)/5-4-(x-(x-1)/5-(x-(x-1)/5-2) | | 4-2y+8y= | | 4x-3=-6x+4 | | -9x=-2−10x | | -.65x+0.45x=5.4 | | -9z=-2−10z | | 7q=6q+10 | | 18x+54=18x+9 |

Equations solver categories